Faktor Organisasi yang Mempengaruhi Pelaksanaan Audit Maternal - Prita Muliarini; Edi Sumarsono (Research Center and Case Clearing House PPM School of Management, 2021)
Maternal audits are part of a change in health care organizations. However, complicated and rigid bureaucracy resulting in difficulties for the organization to accept change without clear and convincing scientific evidence. The maternal mortality remains high, indicating that the maternal audit is not optimal. Often audit recommendations are not implemented so that the expected changes do not occur. This study aims to find suboptimal organizational aspects in the implementation of audits to encourage all parties to collaborate in sustainable, targeted and planned changes. This is a qualitative research with a narrative review approach using secondary data from the previous seven articles. Articles were analyzed to find various obstacles and constraints on maternal audit, and then categorized based on the context of organizational behavior, namely individual, group and structure. This study identified complexities in maternal auditing, interrelated between individual, group and structural aspects, including problems of persecution, low cooperative behavior, and political policies. Those have a major impact on efforts to reduce maternal mortality. Therefore, it requires clinical and non-clinical interventions, as well as political, in accelerating the reduction of maternal mortality. The arrangement of policies, analysis processes, and follow-up on maternal audits must involve every element of the organization, both individuals and groups, in the organizational structure.